Comparative studies reveal variability in the use of tidal stream environments by seabirds. (July 2017) - Waggitt, James J.; Robbins, Alexandra M.C.; Wade, Helen M.; Masden, Elizabeth A.; Furness, Robert W.; Jackson, Angus C.; Scott, Beth E.
Abstract: The global increase in tidal stream turbine installations creates a need to identify and mitigate any impacts on seabird populations. Within Scotland, UK, the vulnerability of black guillemots Cepphus grylle and European shags Phalacrocorax aristotelis is dependent on their tendency to exploit microhabitats characterised by fast mean horizontal current speeds (≥2 ms –1 ), and tidal states with maximum current speeds, within tidal stream environments. Identifying consistencies in their relative use of different microhabitats (fast versus slow mean horizontal current speeds) and tidal states (increasing/decreasing versus maximum currents) across these habitats could assist risk assessment and mitigation measures at both a regional and development site level. Datasets from shore-based surveys collated across 6 tidal stream environments showed that the probability of detecting foraging black guillemots and European shags tended to be higher in fast and slow microhabitats, respectively. However, differences between microhabitats were reversed and/or marginal in 3 out of the 5 sites used for each species. Differences between tidal states were almost always marginal. These variabilities show that a species' vulnerability could differ greatly among development sites, and environmental impact assessments (EIA) must quantify habitat-use using dedicated and site-specific surveys to reduce uncertainty. However, a greater understanding of the mechanisms underlying variation in the use of tidal stream environments is needed when selecting a suite of potential development sites that reduce the possibility of population-level impacts. The current collection of physical and biological data across tidal stream environments could therefore prove invaluable for the protection of seabird populations.